2015
DOI: 10.5480/14-1385
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from the Field: Bringing Nurse Leaders into the Classroom

Abstract: Leadership is a vital component of nurses' careers, and baccalaureate nursing programs are required to include leadership competencies in undergraduate nursing education. To design learning experiences that emphasize professional identity formation, nurse leaders were invited as guest speakers in a senior-level didactic leadership course, but scheduling o en interfered with participation. To inspire students and maximize nurse leaders' time, recorded video was investigated as a solution. Following videotaped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The analysis of the articles addressing the theme showed that the involvement of students is notorious, thus stressing the importance of teaching leadership in undergraduate training (1) . Video resources were used, for example, to bring successful and recognized leaderships to the nursing area of the American Midwest into the classroom at the University of Wisconsin in the United States (6) . Students participated in the formulation of questions to be asked to leaders, recording of interviews, and editing of videos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the articles addressing the theme showed that the involvement of students is notorious, thus stressing the importance of teaching leadership in undergraduate training (1) . Video resources were used, for example, to bring successful and recognized leaderships to the nursing area of the American Midwest into the classroom at the University of Wisconsin in the United States (6) . Students participated in the formulation of questions to be asked to leaders, recording of interviews, and editing of videos.…”
Section: Discussionmentioning
confidence: 99%
“…Perspectives From the Field: Bringing Nurse Leaders Into the Classroom (6) Semi-structured interviews, recorded on video, to "take" leadership into the classroom.…”
Section: Use Of Audiovisual Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplaces increasingly report students are entering the workplace lacking necessary skills (Lutz, 2017;Rateau, Kaufman, & Cletzer, 2015), therefore, it's important to examine curriculum and determine changes needed to lessen the gap. Sortedahl & Imhoff (2016) report barriers exist for bringing experts into the classroom and suggest using live conferencing tools or videos. Having guest lectures is a great way to bring course content knowledge into the classroom, however, instructors can't rely on guest lectures to be available semester-aftersemester, therefore we created videos that would be embedded within the course.…”
Section: Introductionmentioning
confidence: 99%